ON PARTICULAR ASPECTS OF AGRICULTURAL LEASE FUNDING - R. Dimitrova (Trakia Journal of Sciences)
The present article presents some of the aspects inherent to lease as an alternative method for funding farmers when it comes to finance lease. As a matter of fact, this type of lease is profitable in agriculture when it comes to delivering and using high-tech fixed assets.